Improve Accreditation, Regulation, and Quality Standards : For Equitable Care Amidst Rapid Growth and Urbanization - World Bank Group (World Bank, Washington, DC, 2019)
Urbanizing countries can struggle to ensure uniform minimum standards of care quality particularly when the private sector grows quickly but unevenly, with limited government capacity for robust oversight and regulation and limited consumer ability to differentiate between high-and low-quality care. Accreditation and reaccreditation standards in the public sector sometimes do not extend to the private sector, while private sector accreditation bodies can be of mixed quality and subject to abuse. The lack of evidence-based care protocols can also lead to overtreatment, particularly in the context of rising incomes and parallel increases in health-seeking behavior. New approaches are needed to create and apply more universal quality standards while enabling patients to make educated choices about where to seek care.